H2/CH4/CO2-tolerant properties of SrCo0.8Fe0.1Ga0.1O3 − δ hollow fiber membrane reactors for methane partial oxidation to syngas - Meng, X.; Bi, X.; Meng, B.; Yang, N.; Tan, X.; Liu, Lihong; Liu, Shaomin (Elsevier, 2015)
Oxygen permeable ceramic membranes have potential applications as the high temperature membrane reactors for cost-effective syngas production from methane partial oxidation. The prerequisite to realize this potential is that the membrane must be chemically stable at high temperatures in atmospheres containing reducing or acidic gases. To improve the stability of conventional perovskite (SrCo0.8Fe0.2O3-d) ceramic membranes, a doping strategy has been adopted. For this purpose, an asymmetric SrCo0.8Fe0.1Ga0.1O3-d (SCFG) hollow fiber membrane has been fabricated. Its respective oxygen permeability is tested using helium, carbon dioxide, hydrogen and methane as sweep gases, which are the main gas components during the partial oxidation of methane (POM) to syngas. The oxygen permeability of the as-prepared SCFG hollow fiber membrane is up to 3.75mL·min-1·cm-2 at 1000°C when supplied with air as the feed and swept by He, while it declines to 1.85mL·min-1·cm-2 when swept by CO2. Whereas, the oxygen permeation fluxes increase to 3.98 and 3.81mL·min-1·cm-2 at 1000°C, respectively, when the membrane is swept by the reducing gases such as 4% H2-96% He and 20% CH4-80% He, keeping a stable operation for 220h. During the membrane reactor (an integrated separation-reaction process) performance for the POM reaction using the SCFG hollow fiber packed with Ni-Al2O3 catalysts, the ratio of H2/CO, the CH4 conversion, the selectivity of CO and the oxygen permeability are 2.08, 100%, 33%, and 4.14mlmin-1 cm-2, respectively upon steady operation for 23h at 800°C. The promising stability of SCFG membranes during POM reactions has been attributed to the stabilizing effect provided by the doped gallium oxide, which acts as an anchor for the perovskite structure to maintain the integrity of the crystal lattice structure in the reducing atmosphere.